2018
DOI: 10.4103/jispcd.jispcd_438_17
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment need in higher primary schoolchildren of Central Bengaluru, India

Abstract: Aims and Objective:The aim of this study was to evaluate the orthodontic treatment need in 11–14-year-old schoolchildren of Central Bengaluru, India, using the index of orthodontic treatment need (IOTN) and to analyze the treatment needs between males and females and correlation between the esthetic to aesthetic (AC) and dental health component (DHC) of IOTN.Materials and Methods:The sample comprised 500 schoolchildren (187 females and 313 males) who had not undergone orthodontic treatment. No radiographs, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…With regard to a moderate need for therapy, there were slightly fewer males (23.9%) than females (30%), while in the category of those who needed or necessarily required therapy, there were fewer male (19.5%) than female (26.7%) respondents. Most studies did not find a statistically significant difference in the need for therapy between genders (8,9). By comparison, a study conducted 10 years ago in Bosnia and Herzegovina found a statistical difference between girls and boys according to the dental component of this index (6).…”
Section: Discussionmentioning
confidence: 97%
“…With regard to a moderate need for therapy, there were slightly fewer males (23.9%) than females (30%), while in the category of those who needed or necessarily required therapy, there were fewer male (19.5%) than female (26.7%) respondents. Most studies did not find a statistically significant difference in the need for therapy between genders (8,9). By comparison, a study conducted 10 years ago in Bosnia and Herzegovina found a statistical difference between girls and boys according to the dental component of this index (6).…”
Section: Discussionmentioning
confidence: 97%
“…Takie właśnie właściwości posiada wskaźnik IOTN, który jest na tyle obiektywny, że pozwala porównać potrzeby lecznicze w zależności od różnych czynników, takich jak np. płeć czy wiek (10,25,40).…”
Section: Dyskusjaunclassified
“…In epidemiological studies on the prevalence of malocclusions and the orthodontic treatment needs, it is essential to use indices that are as little subjective as possible and allow comparisons between different populations (14). The IOTN has such properties, and it is objective enough to compare treatment needs according to various factors, such as gender or age (10,25,40).…”
Section: Dyskusjamentioning
confidence: 99%
“…The total sample size obtained from 10 primary studies was more than nine thousand [49][50][51][52][53][54][55][56][57][58]. Overall pooled prevalence for any type of treatment need arising from malocclusion was 60.4% (CI 49.2, 71.1).…”
Section: Index Of Orthodontic Treatment Needsmentioning
confidence: 99%